The edge flaking of tungsten carbide hardmetal cermets under repetitive impact loading - Du Randt, Deon (Centre for Materials Engineering, 2024)
Repetitive impact tests were carried out in order to determine the edge flaking performance of several grades of hardmetal cermets. In an attempt to understand the geometry and characteristics of the crack propagation glass was impacted. Various types of cracking are observed in the glass including crushing, lateral cracking, median cracking and Hertzian cone cracking. The results of the glass impacting were then compared with those observed in the hardmetal cermets. Hertzian cone cracking dominates in the cermets. The fractography of the crack surfaces and crack paths, occurring in the cermets, have been studied in order to explain the edge flaking performance. Contiguity and mean-free path are found to have important influences on the edge flaking performance. The performances of the various grades of hardmetal cermets are compared in an attempt to rank them in relation to their susceptibility to edge flake.